PEROLEHAN TANAH ATAS TANAH ULAYAT MASYARAKAT HUKUM ADAT PAPUA DALAM PROGRAM MIFEE (MERAUKE INTEGRATED FOOD AND ENERGYE STATE) DITINJAU DARI PERSPEKTIF HUKUM AGRARIA - Rika Maryam (J-LEE - Journal of Law, English, and Economics, 2023)
This journal aims to determine the process of acquiring land for customary land in the Merauke Integrated Food and Energy Estate (MIFEE) program. whether it is in line with the principle of land acquisition in national agrarian law, and to find out the effect of customary law that arises if customary land is transferred to public interests. The research method used is an empirical juridical research method. Transfer of customary land rights for the public interest. As well as the potential impact of the Merauke Integrated Food and Energy Estate (MIFEE) Project on the quality of life of local indigenous peoples.